Adaptive Strategies of Fishermen in North Maluku: Navigating the Chal-lenges of the Modern Era - Bastian Abednego kaihulu (Jurnal Ilmu Pendidikan dan Humaniora, 2024)
The fishing industry in North Maluku faces multifaceted challenges due to modernization, including economic fluctuations, environmental degradation, and social dynamics. To navigate these challenges, fishermen have adopted various adaptive strategies aimed at ensuring the sustainability of their livelihoods and the fishing sector. This research explores the adaptive strategies employed by fishermen in North Maluku and evaluates their effectiveness in addressing the challenges posed by the modern era. Through a mixed-methods approach involving surveys and interviews, data were collected to understand the diversification of livelihoods, adoption of new technologies, changes in fishing practices, and collective action among fishermen. The findings reveal that fishermen in North Maluku engage in multiple income-generating activities, utilize modern fishing equipment, implement changes in fishing techniques, and participate in collective management approaches. While these strategies demonstrate resilience and innovation among fishermen, challenges such as limited access to resources, market constraints, and environmental impacts pose potential limitations. Addressing these challenges requires collaboration among fishermen, government agencies, NGOs, and other stakeholders to promote sustainable practices and ensure the long-term viability of the fishing industry in North Maluku and beyond.